Association between low‐carbohydrate diets and continuous glucose monitoring‐derived time in ranges. Issue 5 (28th February 2023) - Osugi, Keiko; Kusunoki, Yoshiki; Ohigashi, Mana; Kusunoki, Kenji; Inoue, Chikako; Inoue, Maki; Takagi, Ayako; Tsunoda, Taku; Kadoya, Manabu; Konishi, Kosuke; Katsuno, Tomoyuki; Koyama, Hidenori; et al.
ABSTRACT: Aims: Low‐carbohydrate diets have become popular in the general community. The mutual relationship between the percentage of total energy intake from carbohydrates (CHO/E), glycemic control indices, and diabetes complications remains unclear. Materials and Methods: This cross‐sectional study included 177 patients with type 2 diabetes mellitus who regularly visited outpatient clinics. In this study, dietary questionnaires were used to assess the intake ratio of the three macronutrients, and the low‐carbohydrate‐diet score was calculated. We investigated the association between the low‐carbohydrate‐diet score, continuous glucose monitoring (CGM)‐derived short‐term glycemic control indices, and diabetes complications in patients with type 2 diabetes mellitus. Results: The results are presented as medians (interquartile ranges) unless otherwise stated. Hemoglobin A1c was 7.1% (6.6–7.7%), CGM‐derived time in range (TIR) was 75.3% (62.8–87.0%), body mass index (BMI) was 24.0 (22.1–26.3) kg/m 2, and CHO/E was 49.8% (44.8–55.6%). BMI, triglycerides, and CGM‐derived time above range decreased significantly with increasing low‐carbohydrate‐diet scores. However, no significant association was found between the low‐carbohydrate‐diet score and glycemic control indices, including TIR, mean amplitude of glycemic excursions, and vascular complications of type 2 diabetes mellitus. Conclusion: Moderate‐carbohydrate diets positively impact weight control and lipid metabolism but may have a limited effect on short‐term glycemic variability in Japanese patients with type 2 diabetes mellitus. Abstract : The effects of low‐carbohydrate diets in patients with type 2 diabetes were evaluated. The low‐carbohydrate‐diet score was not associated with time in range or glycemic variability indices derived from continuous glucose monitoring.